Urea and ascorbic acid as ameliorators of cement dust toxicity in Oryza Sativa Var. B.P.T.5204 - Babu Rao, Nirmala; Anuradha, T; Chuhaan, Laxmi Poornima; Omkar, A C (Recent Research in Science and Technology, 2015)
The present study is an attempt to find out the amelioration of urea and ascorbic acid on the inhibitory effect of cement dust on Oryza Sativa (Var. B.P.T.5204). The observations have shown that rice was quite sensitive to cement dust when applied at 3g/m2 daily from three leaf stage until harvest of the crop. The response was analysed in terms of number of leaves, total height, biomass and panicle characters. Urea and ascorbic acid were observed to be quite potent in reverting the inhibitory effect of cement dust. Urea could bring the maximum recovery in shoot and root biomass. These two substances were very useful in reverting the effect of cement dust in terms of height of the plant. Urea increased seed weight upto 35% while ascorbic acid upto 13.4%.